The Ethics of Privacy and Consent in Anthrozoological Investigations - Szydlowski, Michelle; Hooper, Jes; Oxley Heaney, Sarah; Hill, Kristine (Privacy Studies Journal, 2026)
Protecting the safety and privacy of participants seems to be an obvious goal for social science researchers. Vital to this protection is the oversight of ethical or institutional review committees tasked with ensuring the safety and privacy of both researcher and participant. However, otherthanhuman animals are often overlooked or entirely absent from official institutional or ethics board considerations. How, then, can researchers ethically proceed with fieldwork while still ensuring their participants are protected? Is it up to the researcher alone to decide what is ‘ethical’ and how to protect the privacy of informants? This paper problematizes research ethics procedures through an examination of the review process, fieldwork, and dissemination practices of several anthrozoologists. Rather than approaching privacy through a human-otherthanhuman binary lens, the authors suggest that privacy and consent should instead be considered at the level of each individual being.